Isomerism of Cycloserine and Its Protonated Form. Issue 4 (24th February 2014) - Fraschetti, Caterina; Filippi, Antonello; Borocci, Stefano; Steinmetz, Vincent; Speranza, Maurizio
Abstract A comprehensive ab initio investigation has been performed on the structure and stability of the isomers of cycloserine and its protonated forms in the unsolvated state. Many conformers of cycloserine in the ketonic (K), enolic (E4 and E2), and zwitterionic (Z7 and Z2) forms have been characterized. Enols E2 are only a few kilocalories per mole less stable than the K isomers. Enols E4, as well as Z7 and Z2 zwitterions, are several tens of kilocalories per mole less stable than K. All the above isomeric structures exhibit pronounced isoxazolidine ring puckering, which generates very rich conformeric landscapes. The relative stability of the conformers of K, E2, and E4 responds essentially to a complex balance between the attractive and repulsive electrostatic interactions among their functional groups. The preferred site of protonation of cycloserine in the gas phase has been also investigated computationally and experimentally by IR multiphoton dissociation (IRMPD) spectroscopy. The most basic center of cycloserine is the N(7) nitrogen atom (proton affinity (PA)=215.3 kcal mol−1). Another important basic site is the O(6) oxygen atom (PA=213.0 kcal mol−1). Their most populated conformers have been identified by IRMPD spectroscopy. Their predominance responds to the electrostatic interactions among the functional groups of the protonated molecule.